Hydrophobic inducers to enhanced surfactin production using cassava wastewater as low-cost culture medium: a prospection on new homologues - Schmidt, Vanessa Kristine de Oliveira (2022)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Química, Florianópolis, 2022.